PROCESSING PARACETAMOL-5-NITROISOPHTHALIC ACID COCRYSTAL USING SUPERCRITICAL CO2 AS AN ANTI-SOLVENT - TJANDRAWINATA, RAYMOND R.; HIENDRAWAN, STEVANUS; VERIANSYAH, BAMBANG (International Journal of Applied Pharmaceutics, 2019)
Objective: A new method of cocrystallization based on the use of supercritical carbon dioxide (CO2) as an anti-solvent was explored. In the present study, we investigate and analyze paracetamol (PCA)-5-nitroisophthalic acid (5NIP) cocrystal produced using supercritical anti-solvent (SAS) process. Methods: PCA-5NIP cocrystals prepared by SAS cocrystallization were compared to those produced using traditional solvent evaporation by rapid evaporation (RE) process. The cocrystals produced were characterized using powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), polarized light microscopy (PLM), Fourier Transform Infrared (FTIR) spectroscopy, particle size analysis and scanning electron microscopy (SEM). Results: The products obtained from SAS and RE process exhibited identical PXRD spectra and were distinguishable from the individual compounds, indicating the formation of a new phase. DSC analysis revealed that PCA-5NIP cocrystals from each method possess similar melting point which lies between the melting points of the parent compounds. Cocrystal particles with a mean diameter of 4.66 µm were produced from SAS process, which was smaller than those produced by traditional solvent evaporation method with a mean diameter of 38.09 μm. Conclusion: This study demonstrates the ability of SAS process to produce the submicron size of PCA-5NIP cocrystal with altered physicochemical properties in a single step process.